Valuing Liberty or Equality? Empathetic Personality and Political Intolerance of Harmful Speech - Harell, Allison; Hinckley, Robert; Mansell, Jordan (Frontiers in Political Science, 2021)
Political tolerance is a core democratic value, yet a long-standing research agenda suggests that citizens are unwilling to put this value into practice when confronted by groups that they dislike. One of the most disliked groups, especially in recent times, are those promoting racist ideologies. Racist speech poses a challenge to the ideal of political tolerance because it challenges another core tenet of democratic politics – the value of equality. How do citizens deal with threats to equality when making decisions about what speech they believe should be allowed in their communities? In this article, we contribute to the rich literature on political tolerance, but focus on empathy as a key, and understudied, personality trait that should be central to how – and when – citizens reject certain types of speech. Empathy as a cognitive trait relates to one’s capacity to accurately perceive the feeling state of another person. Some people are more prone to worry and care about the feelings of other people, and such empathetic people should be most likely to reject speech that causes harm. Using a comparative online survey in Canada (n=1555) and the United States (n=1627) conducted in 2017, we examine whether empathetic personalities - as measured by a modified version of the Toronto Empathy Scale - predict the tolerance of political activities by "least-liked" as well as prejudicially motivated groups. Using both a standard least-liked political tolerance battery, as well as a vignette experiment that manipulates group type, we test whether higher levels of trait empathy negatively correlate with tolerance of racist speech. Our findings show that empathy powerfully moderates the ways in which citizens react to different forms of objectionable speech.